Pendred syndrome: Advances in diagnostics and unresolved therapeutic challenges - Olga Domańska; Kinga Brzdęk; Michał Brzdęk; Szymon Wiśniewski; Wiktor Baran (Problemy Pielęgniarstwa)
Pendred syndrome remains a condition characterised by numerous complexities and unresolved aspects despite significant advancements in understanding its aetiology and clinical manifestations. The aim of the study was to summarise the latest reports on this autosomal recessive disorder. While typical mutations underlying the syndrome and their implications on cellular function have been elucidated, there are still many unknowns surrounding the disease. Although a typical clinical profile of Pendred syndrome patients has been established, ongoing research continues to uncover new pathomechanisms attributed to these mutations. While diagnostic approaches and clinical guidelines have been refined, effective treatment modalities remain elusive. Despite our enhanced understanding of the disease, the development of targeted and efficacious therapies for Pendred syndrome has yet to be achieved. In summary, while progress has been made in unravelling the intricacies of Pendred syndrome, further research is warranted to bridge existing knowledge gaps and find treatment for this disorder.